ERIC-PCR genotyping of field isolates of Salmonella enterica subsp enterica serovar Gallinarum biovars Gallinarum and Pullorum - Secundo de Souza, Andrei Itajahy [UNESP]; Freitas Neto, Oliveiro Caetano de [UNESP]; Alves Batista, Diego Felipe [UNESP]; del Pilar Celis Estupinan, Anny Lucia [UNESP]; Almeida, Adriana Maria de [UNESP]; Barrow, Paul Andrew; Berchieri, Angelo [UNESP] (Taylor & Francis Ltd, 2015)
Salmonella Gallinarum (SG) and Salmonella Pullorum (SP) have been classified as biovars belonging to Salmonella enterica subsp. enterica serovar Gallinarum. Genetic diversity among isolates of the same biovar can be detected by DNA fingerprinting techniques which are useful in epidemiological investigations. In this study, we applied the PCR amplification of Enterobacterial Repetitive Intergenic Consensus sequences (ERIC-PCR) to analyse 45 strains of SG and SP, most of which were isolated from diseased poultry of different Brazilian regions over a period of 27 years until 2014. The ERIC-genotypes obtained were used to describe the epidemiological relationship amongst the strains. Our findings showed that there were six ERIC-patterns for SG strains at 80% similarity. In addition, some of the SG isolates recovered from different regions and years clustered with 100% similarity, suggesting that transfer of genotypes between these regions has taken place. The commercial rough vaccine strain 9R showed a unique profile. Meanwhile, more genetic diversity was observed among SP strains where ten ERIC-patterns were also formed at 80% similarity.